The Influence of Chief Executive Officer Attributes and Board Independence on Earnings Management Practices - Sri Retnoningsih; Teguh Widodo Adrianto; Khoiriyah Khoiriyah; Khoirotunnisa Khoirotunnisa (Business and Applied Management Journal, 2026)
Earnings management remains a major concern because it reduces the credibility of financial reporting and can mislead stakeholders' decision-making. Although previous research has examined the relationship between CEO characteristics and earnings management, empirical findings remain inconclusive, particularly regarding the role of board independence in strengthening or weakening this relationship. Therefore, this study aims to examine the effects of CEO financial expertise, CEO compensation, CEO nationality, and CEO gender on earnings management, and the moderating role of board independence. Using a quantitative research design, this study analysed 439 firm-year observations in manufacturing companies listed on the Indonesia Stock Exchange during 2020–2023. Data were analysed using multiple regression and Moderated Regression Analysis (MRA). The results show that CEO compensation, CEO nationality, CEO gender, and board independence significantly influence earnings management, whereas CEO financial expertise does not. Board independence significantly moderates the relationship between CEO attributes and earnings management. The integrated model explains 78% of the variance in earnings management (R² = 0.78). These findings contribute to the corporate governance literature by providing empirical evidence that board independence strengthens governance mechanisms that mitigate opportunistic managerial behaviour.